Broadening the discourse on small-scale generation: an investigation into public opinion of embedded rooftop photovoltaic systems in Stellenbosch - Morar, Geeta Sara Creecy (Stellenbosch : Stellenbosch University, 2017)
Thesis (MPA)--Stellenbosch University, 2017.